ANALISIS PEMILIHAN SERENTAK KETUA RW DAN KETUA RT KOTA MAKASSAR DITINJAU DARI ASPEK ETIKA POLITIK - Putri Nadia Esa; Siman juntak; Lilik Noor Yuliati (Jurnal Pallangga Praja (JPP), 2020)
Business environment is in a dynamic condition with strong intensity of competition that requires companyto continually make improvements and update for achieve their competitive advantage compared to competitors. The competitive advantages must be felt by customer to make direct impact for company especially in terms of increasing sales volume. Customer focus of the company come from new customer, customer who have never used a company’s product or service or customer who have previously used the company’s product or service. The car loan company which is the object of research is one of the companies engaged in financial services. In the previous year the business process strategy carried out by company X more focused on strategies for acquiring new customer (customer acquisition). This can be seen from the portfolio of customer who take credit at the company X nearly 80.0 percent are new customer and only 20.0 percent customer who have previously used company products or service. On the other hand company X has portfolio target for customer who have previously used company product or service by 30.0 percent, but for the past five years the target has not been achieved. There are seven latent variables in this study, customer perceived value (CPV), corporate image (CI), service quality (SQ) and switching barrier (SB) as an exogenous variables. Customer retention (CR) as an endogenous variable. Customer satisfaction (CS) and customer trust (CT) as an intervening variables.The objectives of this study are (1) to identify the characteristics of customer who take car loan in companyX, (2) analyze the effect of customer perceived value, corporate image and service quality on customersatisfaction, (3) analyze the direct effect of switching barriers on customer retention, ( 4) analyze the directinfluence of customer satisfaction on customer retention and the indirect influence of customer satisfactionon customer retention through customer trust, (5) formulate managerial implications that can be applied bycompany X in implementing strategies to increase customer retention.This research was conducted at one of the car loan companies in Jakarta. This research has been completedfrom February to July 2019. The approach used in this research is survey of company X customer. The typeof data used is primary data originating from filling out the questionnaire. The sampling technique usedwas purposive sampling. The sample requirements in this study are customer with priority segmentation inJabodetabek area who have made a car loan at least once and for five years since the end of their creditperiod they have never made credit again. Data processing techniques used in this study are StructuralEquation Modeling (SEM) with AMOS and descriptive analysis using SPSS and Microsoft Excel.The result showed that the majority of customer who took car loan at company X are male (82.3%) with ages31-40 years (51.0%) and were married (71.6%). The education level of company x customer is dominatedby S1 (65.5%) who work as an employee (43.2%). The biggest monthly expenditure customer is in therange of Rp.4.000.001-5.000.000 (54.8%). Based on vehicle ownership data show that customer who havea number of vehicle as much as one unit more than the other number (80.0%) with the most owned vehiclebrand is Toyota (63.5%). Company X, BCA Finance (BCAF) and Mandiri Tunas Finance (MTF) are carloan companies that become top of mind. Currently the credit company that are used more by customer areBCA Finance (BCAF) because BCA Finance (BCAF) has lower interest rates. The main advantage of thecompany X now is a fast credit process (21.3%). Most customer are aware of the special offer provided bycompany X for loyal customer (68.7%). The known special offer is in the form of credit ceiling (55.9%). Butit turns out that the special offer considered attractive to customer is the special interest (62.4%).Based on the evaluation of the suitability model, the model used in this study is fit so it is feasible to testthe hypothesis. Based on the evaluation of indicator validity test, there are 17 indicators that show results>0.5 or valid. The result of this study are that customer perceived value has a positive and significant effecton customer satisfaction; corporate image has a positive and significant effect on customer satisfaction;service quality has a positive and significant effect on customer satisfaction; switching barrier has a positiveand significant effect on customer retention; customer satisfaction has no significant effect on customerretention; customer satisfaction has a positive and significant effect on customer trust and customer trusthas a positive and significant effect on customer retention.Managerial implications for company X are making customer grouping, customer sales target and makingspecial products based on customer grouping. Pricing aspect need in making these special products. Inaddition, company need to create a channel for delivering information to customer, one of which can usetelesales mechanism. As a media reminder to customer, company can use Short Message Service (SMS) orwhatsapp blast.